A pajelança cabocla: aspectos da tradução entre a feiticiaria e xamãs - BRANCO, Rosanne Cordeiro de Castelo (Universidade Federal do Pará, 2020)
The present work consists in approaching the character of the translation in the universe of the language resulting from the study on the representation of the Amazonian imaginary present in the narratives of Zeneida Lima (1992, 2001), a pajé from the island of Marajó, in its interrelation with Caruanas or enchanted. The research deals with the anthropological aspects of humans and nonhumans from the standpoint of theoreticians such as Câmara Cascudo (1956), Viveiros de Castro (1993), LéviStrauss (2003), Evelyn Zea (2008) and Bruna Franchetto (2012) As are the ideas of philosophers and theorists such as Walter Benjamin (2008), Paul De Man (1989), Derrida (1972) and Venuti (1995). In the context of the narrative on the pajelança cabocla, the pajé Zeneida Lima receives, in mediumistic sessions, nonhuman beings entering a process of trance and ecstasy, where it counts on the presence of a translator called in the narrative of 'transmitter', which translates to Language of the enchanted to the understanding of the men who inhabit the earth, in a cosmological dimension.